2020
DOI: 10.5194/acp-20-6671-2020
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric chemical loss processes of isocyanic acid (HNCO): a combined theoretical kinetic and global modelling study

Abstract: Abstract. Isocyanic acid (HNCO) is a chemical constituent suspected to be harmful to humans if ambient concentrations exceed ∼1 ppbv. HNCO is mainly emitted by combustion processes but is also inadvertently released by NOx mitigation measures in flue gas treatments. With increasing biomass burning and more widespread usage of catalytic converters in car engines, good prediction of HNCO atmospheric levels with global models is desirable. Little is known directly about the chemical loss processes of HNCO, which … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 91 publications
3
21
3
Order By: Relevance
“…Globally, similar high concentrations are predicted in this study. However, we predict higher concentrations in Indonesia than Rosanka et al (2020d), who reported that ambient HNCO conditions of 1 ppb are exceeded for less than 30 days in Indonesia in 2011. The year 2011 is known to have low biomass burning emissions in this region (van der Werf et al, 2017).…”
Section: Pollution and Toxic Conditionscontrasting
confidence: 51%
See 4 more Smart Citations
“…Globally, similar high concentrations are predicted in this study. However, we predict higher concentrations in Indonesia than Rosanka et al (2020d), who reported that ambient HNCO conditions of 1 ppb are exceeded for less than 30 days in Indonesia in 2011. The year 2011 is known to have low biomass burning emissions in this region (van der Werf et al, 2017).…”
Section: Pollution and Toxic Conditionscontrasting
confidence: 51%
“…In order to properly represent this toxic constituent within EMAC, MOM has been extended to represent the atmospheric chemistry of HNCO. For this, the mechanism proposed by Rosanka et al (2020d) is implemented into MOM. Their mechanism includes formamide as an additional chemical source of HNCO and chemical mechanisms for nitromethane, methylamine, dimethylamine, and trimethylamine.…”
Section: Atmospheric Chemistrymentioning
confidence: 99%
See 3 more Smart Citations